Razmišljanja o geografiji - Vrišer, Igor (Geografski vestnik, 1979)
In the paper the author deals the essence and object of geography, the position of geography in the general classification of sciences, the internal composition of geography, the influences and the reflections of different philosophical cognitive approaches to geography, the application of the geography in the societal life and the role of geography as a nacional importance.
Keywords: geografija; geografska teorija; geographical theory; geography